ANALISIS PROGRAM MAGANG, MINAT PROFESI GURU, DAN LOCUS OF CONTROL INTERNAL TERHADAP KESIAPAN MENJADI TENAGA PENDIDIK MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI STKIP PGRI TULUNGAGUNG YANG SEDANG MENEMPUH SKRIPSI TAHUN 2017/2018 - Fitri Nur Kholifah; Nafik Umurul Hadi (Universitas Nusa Cendana, 2017)
According to the Minister of National Education Regulation No. 16 of 2007 on AcademicQualification and Teacher Competency Standards, as for the various competencies of teachers thatmust be owned by Teachers include: Pedagogic Competency, Personality Competence, SocialCompetence and Professional Competence. Based on an open questionnaire, some of the studentssaid that with the provisions that have been obtained from STKIP PGRI Tulungagung, they areready to work as educators, but some students say that they feel not ready to be an educator forvarious reasons. The purpose of this study is to analyze the influence of partially or simultaneouslyInternship Program, Teacher Profession Interest, and Locus Of Internal Control Against ReadinessBecoming Student Educator Economics Study Program STKIP PGRI Tulungagung Who TakingThesis Year 2017/2018. The research method used is descriptive method with quantitativeapproach. The analytical technique used multiple linear regression analysis. Based on the results ofthe study concluded that: There is a significant influence partially or simultaneously InternshipProgram, Teacher Profession Interest, and Locus Of Internal Control Against Readiness BecomingStudent Educator. The value of coefficient of determination (adjusted R2) of 0.49, it means 49%Readiness Becoming Student Educator is influenced by Internship Program, Teacher ProfessionInterest, and Locus Of Internal Control.Keywords: Internship Program, Teacher Profession Interest, Locus Of Internal Control, Readinessto Become Educator